Isolation of single HIV-1 Envelope specific B cells and antibody cloning from immunized rhesus macaques - Wang, Zijun (J Immunol Methods, 2019)
Antibody cloning from single B cells is an essential tool for characterizing humoral immune responses and obtaining valuable therapeutic and analytical reagents. Antibody cloning from individuals with high serologic titers to HIV-1, Influenza, Malaria and ZIKV has led to new insights that inform vaccine design efforts. In contrast to humans and mice, less is known about antibody cloning from single B cells in macaques. Here, we describe a protocol to identify and purify single antigen-specific macaque B cells, and subsequently clone and produce macaque monoclonal antibodies. The sorting strategy requires the use of a combination of fluorochrome labeled antigens and omission of anti-IgG antibodies that can interfere with antigen binding and vice versa. Optimized methods for macaque antibody gene amplification, DNA preparation for antibody production and antibody screening by ELISA are also presented.